Ergo-aesthetic approach through senses and behavioral assessment - Ezran Zainal Abdullah, Muhamad; Aidil Azlin Abd Rahman, Khair (International Journal of Engineering and Technology, 2018)
In general, the concept of ergo-aesthetic discloses the equilibrium of human behavioral character with form, shape, and symbolism inside a designed product. In fact, this harmony synthesis can be achieved throughout responses of behavior and senses inside a design process. Through the adaptation of ergo-aesthetic, humans will be able to achieve greater satisfaction with the designed product as they will positively interact and respond proportionally to it. In this context, ergo-aesthetic principles will replace the traditional method of evaluating and adapting ergonomic and aesthetic into the design process to achieve a better output product. Essentially, ergonomic and aesthetic are fundamental components that need to be considered throughout the design process procedures. The synergy between these two aspects may facilitate in optimizing the efficiency of the design process which will contribute to a higher output quality. Additionally, behavior and culture are also significant as they function as bonding agents for ergonomic and aesthetic to merge harmonically. Thus, implementing ergo-aesthetic principles into design process through behavior and cultural perspectives may lead to the enhancement of the output quality of a product.Â Â